Composition and Condition of Mangrove Forest in Tarnana Island Subdistrict South Jailolo, North Maluku Province - Susanto, Adi Noman; Sabar, Mesrawaty; Abubakar, Salim; Sunarti, Sunarti; Abubakar, Yuyun (Agrikan: Jurnal Agribisnis Perikanan, 2021)
The mangrove ecosystem is one of the main ecosystems in the coastal area which is very productive, but is very vulnerable to changes or external influences. As a vulnerable ecosystem, mangrove ecosystem management has to concern the integration of the community's ecological, economic and socio-cultural aspects so that optimal and sustainable management is achieved. The research objectives were to know the composition of mangrove species, to determine the structure of the mangrove forest community (species diversity, species dominance, uniformity, species density, species cover) and to determine the condition of mangrove forests on Tarnana Island, Jailolo Selatan District. This research was conducted on Tarnana Island, Jailolo Selatan District, and West Halmahera Regency in January - February 2021. The sampling method was carried out using the spot check method. Sampling was carried out at the lowest tide by using 5 line transects and each line transect placed 5 plots. Data analysis included species diversity, species dominance, uniformity, species density and species cover. The composition of mangrove species on Tarnana Island was obtained as many as 8 species, namely Rhizophora apiculata, R. stylosa, Bruguirea gymnorrhiza, Ceriops decandra, Ceriops tagal, Sonneratia alba, Xylocarpus granatum and Avicennia alba. The structure of the mangrove community has moderate species diversity, no dominant species and moderate uniformity. The condition of the mangrove forest on Tarnana Island is in the damaged category with rare density.